Tungku Tigo Sajarangan, Tali Tigo Sapilin: A Strategy Towards World Class University Based on Local Wisdom Perspective - Andi Amri; Zulmi Ramdani; Jaka Warsihna; Lidwina Felisima Tae (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to analyze and describe Tungku Tigo Sajarangan, Tali Tigo Sapilin as an indicator to achieve a world-class university. Descriptive qualitative research methods were used to answer this objective by conducting several procedures such as interviews with the cultural expert of Minangkabau, interviews with the educational experts, direct observation of learning activities in the university, and study the scientific literature. Thematic content analysis was used to find informative descriptions of the data obtained. The results showed that the concept of leadership, customs, and local wisdom originating from Minangkabau culture could become an alternative framework and a formula for the realm of education especially for the universities to become a world-class university. The steps for implementing Tungku Tigo Sajarangan, Tali Tigo Sapilin include four stages namely preparation, implementation, post-implementation, and evaluation.